2005
DOI: 10.1016/j.jacc.2005.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Human Infarcted Heart Muscle by Intracoronary Autologous Bone Marrow Cell Transplantation in Chronic Coronary Artery Disease

Abstract: These results demonstrate that functional and metabolic regeneration of infarcted and chronically avital tissue can be realized in humans by bone marrow mononuclear cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
3
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(203 citation statements)
references
References 33 publications
9
182
3
9
Order By: Relevance
“…As in animal models, they found a reduction in infarct size, an increase in LV function, and wall motion velocity in the treatment group. No change was obvious in the nonrandomized control group (116). Only few other studies with a small number of patients are further reported for stem cell therapy in this indication.…”
Section: Chronic Myocardial Infarction/coronary Total Occlusionmentioning
confidence: 82%
“…As in animal models, they found a reduction in infarct size, an increase in LV function, and wall motion velocity in the treatment group. No change was obvious in the nonrandomized control group (116). Only few other studies with a small number of patients are further reported for stem cell therapy in this indication.…”
Section: Chronic Myocardial Infarction/coronary Total Occlusionmentioning
confidence: 82%
“…A randomized trial in patients with chronic MI showed that LVEF increased by 15% at 3 months post intracoronary BMC therapy, whereas LVEF reduced 1.0% at the same period in control patients. 35 Moreover, this benefit can be sustained for 2.5 years after MI. 36 One or more years after BMC transfer, significantly reduced LVEDV, LVESV, and infarct size were evidenced in treated patients, which suggested that BMC might attenuate left ventricular remodeling after acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…The cell transplantation demonstrated enhanced myocardial perfusion and cardiac function in ischemic hearts of patients with acute or chronic myocardial infarction. [8][9][10][11][12][13] ADSCs contain self-renewing stem cells capable of differentiating in vitro toward osteogenic, adipogenic, myogenic, and chondrogenic lineages when treated with established lineage-specific factors. 14,15 ADSCs have several advantages over other types of stem cells, such as easy accessibility, minimal morbidity upon harvest, and feasibility of extracting clinically relevant numbers of stem cells.…”
Section: Introductionmentioning
confidence: 99%